Would-be places for displaced Afghans – The UNHCR, landless returnees and the enforcement of the national order - Giulia Scalettaris (Revue des Mondes Musulmans et de la Méditerranée)
This article examines the role of the UNHCR in the launch of a scheme fostering the creation of new settlements across Afghanistan in order to accommodate landless returnees. This project entails substantial engineering, aimed at making life possible in inhospitable areas. It thus involves a battle against nature, as well as engaging with the transformation of the Afghan state. The uncertain future of these would-be towns questions the representations about the relationship between people, space and states implied by the ‘national order of things’, that is, a set of normative representations which naturalize the isomorphism between the members of national polities and the territory of their state of citizenship. The nation-state hardly describes the historical process of the formation of the Afghan state, nor Afghan livelihood strategies based on migration. The difficulty experienced in founding these settlements reveals the power relations at work in the way landless Afghan returnees are made ‘dwellers of the world’, and brings into question the role and capacity of an international agency to challenge those relations.